Obesity prevention in a City State: lessons from New York City during the Bloomberg administration - Paul M. Kelly; Paul M. Kelly; Anna eDavies; Alexandra J.M. Greig; Alexandra J.M. Greig; Karen K. Lee; Karen K. Lee; Karen K. Lee (Frontiers Media S.A., 2016)
ObjectiveTo illuminate the key components of multi-sector reform to address the obesogenic environment in New York City during the administration of Mayor Michael Bloomberg from 2002 to 2013, we conducted a case study consisting of interviews with and a critical analysis of the experiences of leading decision makers and implementers.MethodKey informant interviews (N=41) conducted in 2014 were recorded, transcribed, coded and thematically analyzed. Participants included officials from the Health Department and other New York City Government agencies, academics, civil society members and private sector executives. ResultsParticipants described Mayor Bloomberg as a data-driven politician who wanted to improve the lives of New Yorkers. He appointed talented Commissioners and encouraged them and their staff to be bold, innovative and collaborative. Multiple programs spanning multiple sectors, with varied approaches and targets were supported. This study found that much of the work relied on loose coalitions across City Government, with single agencies responsible for their own agendas, some with health co-benefits. Many policies were implemented through non-legislative mechanisms such as executive orders and the Health Code. Despite support from academic and some civil society groups, strong lobbying from industry and an unfavorable media led to some reforms being modified, legally challenged or blocked completely, particularly food environment modifiers. In contrast, reforms of the physical environment were described as highly consultative across and outside government and resulted in slower but more sustained reform.ConclusionsThe Bloomberg administration was a window of opportunity with the imprimatur of the executive to progress a long-term, multi-faceted obesity prevention strategy which has successfully reversed childhood trends. Through the involvement of external researchers and the extensive use of empirical data from a wide range of participants, this study offers a distinctive insight into the ways in which this was achieved. Whilst some of the aspects of the reforms in New York City are unique to that setting at that time, there are important lessons that are transferable to other urban settings. These include: strong and consistent leadership; a commitment to innovative approaches and cross-sectoral collaboration and; and a context to support and encourage this approach.